Understanding Guest Experiences in Remote Luxury Resort: A SERVQUAL Analysis - Seingo, Martha Maraka; Pontolawokang, Theresya Ellen; Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi, 2025)
This study examines guest experiences at Nihi Resort in Sumba, Indonesia, utilizing an adapted SERVQUAL framework to analyze service quality dimensions in a remote luxury hospitality context. Through systematic analysis of guest reviews collected from TripAdvisor, the research employs a qualitative methodology incorporating open, axial, and selective coding techniques to identify patterns in service quality perception. Findings reveal that Assurance Trust is the dominant SERVQUAL dimension in this isolated luxury setting, fundamentally reconfiguring traditional service quality hierarchies. Network visualization analysis demonstrates how Assurance functions as both a direct satisfaction determinant and a mediating variable influencing perceptions across reliability, responsiveness, and empathy domains. This dimensional prioritization reflects the psychological mechanisms activated when guests engage with service providers in unfamiliar, isolated environments characterized by substantial financial investments and limited alternatives. The study contributes to hospitality literature by establishing a contextually sensitive analytical model for understanding service quality in geographically isolated luxury resorts. Strategic implications for management include prioritizing investments in staff competency development, implementing transparent safety communication protocols, and developing specialized training programs addressing cultural sensitivity and interpersonal trust development. These findings advance theoretical understanding of how geographic isolation modulates conventional service quality paradigms while providing luxury hospitality practitioners with evidence-based strategic guidance for resource allocation prioritization.